DEVELOPMENT OF TIME-TEMPERATURE INDICATOR FROM RED PALM OIL AND MAIZE OIL BLENDING - Reza Widyasaputra; Adi Ruswanto; Ngatirah; Sunardi (Jurnal Pangan dan Agroindustri, 2022)
Time-temperature indicator could be used to monitor temperature changes during storage and distribution. The time-temperature indicator with red palm oil and maize oil was evaluated to find the diffusion prediction model and the right oil blending proportion based on activation energy. This research was performed in two stages. Stage 1 was production of red palm oil and maize oil blending in five ratios: A1 (70:30), A2 (60:40), A3 (50:50), A4 (40:60), A5 (30:70) (%v/v). Stage 2 was measurement of diffusion rate, coefficient, kinetics and activation energy in photo paper medium at 4, 29, 37, 44 and 51 °C. The result showed that increasing the temperature could increase diffusion rate and coefficient. The A5 blending proportion had 36.7961 kJ/mol energy activation which were in range of commercial time-temperature indicator (34-50 kJ/mol). The diffusion prediction model was Ln D = -4425.8 – 3.1187.